2001
DOI: 10.1021/bi0019803
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cholesterol with Sphingomyelin in Mixed Membranes Containing Phosphatidylcholine, Studied by Spin-Label ESR and IR Spectroscopies. A Possible Stabilization of Gel-Phase Sphingolipid Domains by Cholesterol

Abstract: The ESR spectra from different positional isomers of sphingomyelin and phosphatidylcholine spin-labeled in their acyl chain have been studied in sphingomyelin(cerebroside)-phosphatidylcholine mixed membranes that contain cholesterol. The aim was to investigate mechanisms by which cholesterol could stabilize possible domain formation in sphingolipid-glycerolipid membranes. The outer hyperfine splittings in the ESR spectra of sphingomyelin and phosphatidylcholine spin-labeled on the 5 C atom of the acyl chain we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 28 publications
9
119
1
2
Order By: Relevance
“…Several experimental data indicate a strong tendency of SM and cholesterol to interact with each other, mainly caused by van der Waals attractive forces between the saturated acyl chain of SM and the rigid cholesterol ring backbone (52,54). In addition, experimental and computational data suggest that hydrogen bonds between SM and cholesterol might facilitate their interaction, presumably via the amide group of SM and the 3-hydroxyl of cholesterol (55,56).…”
Section: Ipc-ergosterolmentioning
confidence: 99%
“…Several experimental data indicate a strong tendency of SM and cholesterol to interact with each other, mainly caused by van der Waals attractive forces between the saturated acyl chain of SM and the rigid cholesterol ring backbone (52,54). In addition, experimental and computational data suggest that hydrogen bonds between SM and cholesterol might facilitate their interaction, presumably via the amide group of SM and the 3-hydroxyl of cholesterol (55,56).…”
Section: Ipc-ergosterolmentioning
confidence: 99%
“…The most compelling evidence for lateral diversity in the bilayer is the presence of lipid rafts, currently defined as dynamic, nano-sized, sterolsphingolipid-enriched assemblies in which protein and lipid content fluctuates on a subsecond time scale (2,3). It is clear that in model membrane systems, sphingolipid and cholesterol selfassociate into liquid-ordered (Lo) phases wherein hydrocarbon chains are longer and more saturated, leading to a thicker, more condensed assemblage that segregates away from liquiddisordered (Ld) unsaturated glycerophospholipids (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The challenge of the raft concept relates to how we rationalize these biophysical principles in the context of the compositional complexity of cell membranes.…”
mentioning
confidence: 99%
“…This idea is supported by theˆnding of SM-and cholesterolrich DRMs in mixtures of TR and vesicles made of PC, SM, and cholesterol (53). SM interacts with cholesterol in bilayers, possibly through hydrogen bonding between the 3b-OH of cholesterol and the carbonyl group of SM (52,56,57). A debate exists around the possibility that the condensation of SM monolayers in the presence of cholesterol indicates a speciˆc interaction between these two lipids.…”
Section: Why Are Drms Not Raftsmentioning
confidence: 99%
“…Others have also suggested that rafts resist solubilization because they exist in the Lo phase. Mixtures of sphingomyelin and cholesterol, two lipids presumably common in rafts, are known to give rise to Lo phases (56). The Lo phase is characterized by translational diŠusion and a high degree of molecular order in the hydrocarbon chains.…”
Section: Why Are Drms Not Raftsmentioning
confidence: 99%